In vitro modeling of glioblastoma initiation using PDGF-AA and p53-null neural progenitors. Issue 8 (16th April 2020) - Bohm, Alexandra K; DePetro, Jessica; Binding, Carmen E; Gerber, Amanda; Chahley, Nicholas; Berger, N Dan; Ware, Mathaeus; Thomas, Kaitlin; Senapathi, U; Bukhari, Shazreh; Chen, Cindy; Chahley, Erin; et al.
Abstract: Background: Imagining ways to prevent or treat glioblastoma (GBM) has been hindered by a lack of understanding of its pathogenesis. Although overexpression of platelet derived growth factor with two A-chains (PDGF-AA) may be an early event, critical details of the core biology of GBM are lacking. For example, existing PDGF-driven models replicate its microscopic appearance, but not its genomic architecture. Here we report a model that overcomes this barrier to authenticity. Methods: Using a method developed to establish neural stem cell cultures, we investigated the effects of PDGF-AA on subventricular zone (SVZ) cells, one of the putative cells of origin of GBM. We microdissected SVZ tissue from p53-null and wild-type adult mice, cultured cells in media supplemented with PDGF-AA, and assessed cell viability, proliferation, genome stability, and tumorigenicity. Results: Counterintuitive to its canonical role as a growth factor, we observed abrupt and massive cell death in PDGF-AA: wild-type cells did not survive, whereas a small fraction of null cells evaded apoptosis. Surviving null cells displayed attenuated proliferation accompanied by whole chromosome gains and losses. After approximately 100 days in PDGF-AA, cells suddenly proliferated rapidly, acquired growth factor independence, and became tumorigenic in immune-competent mice. Transformed cells had an oligodendrocyte precursor-like lineage marker profile, were resistant to platelet derived growth factor receptor alpha inhibition, and harbored highly abnormal karyotypes similar to human GBM. Conclusion: This model associates genome instability in neural progenitor cells with chronic exposure to PDGF-AA and is the first to approximate the genomic landscape of human GBM and the first in which the earliest phases of the disease can be studied directly.